Outcome of patients with cardiogenic shock and previous right ventricular impairment represented by decreased tricuspid annular plane systolic excursion and tricuspid annular plane systolic excursion to pulmonary artery systolic pressure ratio - Rusnak, Jonas; Schupp, Tobias; Weidner, Kathrin; Ruka, Marinela; Egner-Walter, Sascha; Forner, Jan; Bertsch, Thomas; Kittel, Maximilian; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Akın, Ibrahim; et al. (The American journal of cardiology, 2023)
This study investigates the prognostic impact of known decreased ratio of tricuspid annular plane systolic excursion (TAPSE) to pulmonary artery systolic pressure (PASP) and TAPSE in patients with cardiogenic shock (CS). In patients with pulmonary artery hypertension and in critically ill patients, decreased TAPSE and TAPSE/PASP ratio are known to be negative predictors. However, studies regarding the prognostic impact in patients with CS are limited. Consecutive patients with CS from June 2019 to May 2021 treated at a single center were included. Medical history including echocardiographic parameters such as TAPSE and PASP was documented for each patient. The primary endpoint was all-cause mortality at 30 days. Statistical analyses included univariable t test, Spearman's correlation, C-statistics, Kaplan-Meier analyses, and Cox proportional regression analyses. A total of 90 patients with CS and measurement of TAPSE and TAPSE/PASP ratio were included. TAPSE and TAPSE/PASP ratio measured several months before intensive care unit admission were both able to predict 30-day survival in CS patients, and were both lower in 30-day nonsurvivors. TAPSE/PASP ratio <0.4 mm/mmHg (log-rank p = 0.006) and TAPSE <18 mm (log-rank p = 0.004) were associated with increased risk of 30-day all-cause mortality. After multivariable adjustment, TAPSE/PASP ratio <0.4 mm/mmHg was not able to predict 30-day all-cause mortality, whereas TAPSE <18 mm was still significantly associated with the primary endpoint (hazard ratio 2.336, confidence interval 1.067 to 5.115, p = 0.034). In consecutive patients presenting with CS, compared to TAPSE alone, previously determined TAPSE/PASP ratio did not improve risk prediction for 30-day all-cause mortality.